2012
DOI: 10.1016/j.physa.2011.08.063
|View full text |Cite
|
Sign up to set email alerts
|

How altruism works: An evolutionary model of supply networks

Abstract: Recently, supply networks have attracted increasing attention from the scientific community. However, it lacks serious consideration of social preference in Supply Chain Management. In this paper, we develop an evolutionary decision-making model to characterize the effects of suppliers' altruism in supply networks, and find that the performances of both suppliers and supply chains are improved by introducing the role of altruism. Furthermore, an interesting and reasonable phenomenon is discovered that the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A related study found that whether different subjects can achieve cooperation depends on their altruistic preferences and the associated prestige, rather than their benefits [28]. Ge Zehui [29] built an evolution decision model and applied it to the analysis of altruistic attributes of the supply network. The paper points out that considering the altruism attribute is good for suppliers and the supply chain system.…”
Section: Introductionmentioning
confidence: 99%
“…A related study found that whether different subjects can achieve cooperation depends on their altruistic preferences and the associated prestige, rather than their benefits [28]. Ge Zehui [29] built an evolution decision model and applied it to the analysis of altruistic attributes of the supply network. The paper points out that considering the altruism attribute is good for suppliers and the supply chain system.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, such intermediate directed structure property, namely reciprocity [5] , facilitates a great deal of attention from the scientific community. Nowak and Sigmund discussed that the indirect reciprocity would help in building reputation systems, judging morality and eventually promote the cooperation level [6] and benefit the evolution of natural selection [7] in both social environment [8] and supply networks [9] . Pereira et al experimentally discussed that negative reciprocity, because of lower cost and less effort, was somehow more favored than the positive reciprocity [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Loch et al [24] pointed out that the altruistic preference could promote the cooperation among all enterprises in the supply chain and improve the overall systematic efficiency and sustainability. By introducing altruistic preference into the supply chain network, Ge et al [25] found that the performance of both suppliers and supply chain systems was improved. Xiao et al [26] proposed a security system that applied the indirect reciprocity principle to combat attacks in wireless networks, which could significantly reduce the attacker population for a wide range of attacks and outperform the existing direct reciprocity-based systems.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%